Tissue Responses and Wound Healing following Laser Scleral Microporation for Presbyopia Therapy - Liu, Yu-Chi (Transl Vis Sci Technol, 2020)
PURPOSE: To investigate the postoperative inflammatory and wound-healing responses after laser scleral microporation for presbyopia. METHODS: Thirty porcine eyes were used for the optimization of laser intensities first. Six monkeys (12 eyes) received scleral microporation with an erbium yttrium aluminum garnet (Er:YAG) laser, and half of the eyes received concurrent subconjunctival collagen gel to modulate wound-healing response. The intraocular pressure (IOP) and the laser ablation depth were evaluated. The animals were euthanized at 1, 6, and 9 months postoperatively. The limbal areas and scleras were harvested for histologic analysis and immunofluorescence of markers for inflammation (CD11b and CD45), wound healing (CD90, tenascin-C, fibronectin, and HSP47), wound contraction (α–smooth muscle actin [α-SMA]), vascular response (CD31), nerve injury (GAP43), and limbal stem cells (P63 and telomerase). RESULTS: In the nonhuman primate study, there was a significant reduction in IOP after the procedure. Overall, the ablation depth was 76.6% to 81.2% at 1 month and slightly decreased to 71.5% to 72.7% at 9 months. Coagulative necrosis around the micropores, as well as expression of CD11b, CD45, tenascin, fibronectin, HSP47, and GAP43, was distinct at 1 month but subsided with time. Collagen gel treatment significantly suppressed the upregulation of CD11b, CD45, fibronectin, and tenascin-C. The expression of CD90, α-SMA, and CD31 was minimal in all eyes. CONCLUSIONS: The study demonstrated the course of inflammatory and wound-healing responses following laser scleral microporation. The tissue responses were small and self-limited, resolved with time, and were suppressed by concurrent collagen treatment. It provides a useful understanding of this new procedure. TRANSLATIONAL RELEVANCE: The results would be helpful in the laser parameter modification to improve the long-term treatment stability.